Portrait of a contemporary teacher in a new digital reality - Elena A. Petrash; Tatyana V. Sidorova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper actualizes the importance of modifying the portrait of a 21st century teacher, which is being transformed in an era of uncertainty. On the basis of theoretical analysis, the authors fixed the modern requirements for a teacher working in the digital era: professional, creative, information, communication, social competence; multitasking; emotional intelligence; cultural, professional and pedagogical mobility. Differences were identified between the modern teacher and the teacher who worked at school 10 years ago; identified professional risks. During the empirical research, quantitative (questionnaires, content analysis) and qualitative methods (polls, interviews, included and non-included observation, analysis of the teachers creative works) were used. The research involved 300 teachers from the Pskov and Moscow regions, as well as from the city of St. Petersburg. The empirical research carried out made it possible to supplement the teachers professiogram with practice-oriented skills. Based on the results of the research, the authors propose a professional development program for teachers called The Modern Teacher and the Challenges of the 21st Century. The advanced training program for teachers is based on the provisions of the system-activity, anthropological and synergetic approaches, and is implemented through interactive forms of work. The topic of classes, forms of conducting, and the features of interaction with teachers during the courses are described. The practical significance of the study lies in the possibility of meaningful updating and implementation of advanced training programs for teachers working in the digital era. The professiogram of a modern teacher has undergone a transformation: a multi-tasking teacher-manager who owns technical means and knows how to find contact with children living in digital reality becomes a teacher of a new formation.